Preparation of Ni-Mn ferrites magnetic nanoparticles through the ethanol solution combustion-calcination process for the adsorption of methyl blue - Zhongjun Pan; Zhou Wang; Zhixiang Lv (PLoS ONE, 2025)
Ni-Mn ferrites magnetic nanoparticles (MNPs) were successfully prepared through the ethanol solution combustion-calcination process, and characterized by SEM, TEM, XRD, VSM, BET, and FTIR techniques. For smaller particle size and suitable magnetic property, the optimum element ratio of the material was Ni0.9Mn0.1Fe2O4, and the optimal preparation conditions were appropriate ethanol dosage to attain Fe3+ concentrations of approximately 0.85 M, calcination temperature of 400 °C, and calcination time of 2 h, their specific surface area was 136.5 m2/g, and their average particle size and saturation magnetization were 35 nm and 21.66 emu/g, respectively. The adsorption process of methyl blue (MB) onto Ni0.9Mn0.1Fe2O4 MNPs conformed to the pseudo-second-order adsorption kinetic model in the initial concentrations of 100–250 mg/L. In comparison with Langmuir and Freundlich adsorption isotherm models, the Temkin model (R2 = 0.9865) was observed to better demonstrate the state of MB onto Ni0.9Mn0.1Fe2O4 MNPs, revealing that the adsorption mechanism of MB onto Ni0.9Mn0.1Fe2O4 MNPs was the multi-molecular chemical process. The adsorption capacity of Ni0.9Mn0.1Fe2O4 MNPs for MB still maintained about 90% of the initial adsorbance after 6 times cyclic utilization of the nanoparticles by recalcination method, suggesting that Ni0.9Mn0.1Fe2O4 MNPs had excellent regeneration performance. In general, these results coupled with its environmental friendliness attributed the potential candidates for effluent remediation.